Characterization of Interface Between Accurately Controlled Cu‐Deficient Layer and Cu(In, Ga)Se2 Absorber for Cu(In, Ga)Se2 Solar Cells. Issue 8 (16th May 2018) - Nishimura, Takahito; Sugiura, Hiroki; Nakada, Kazuyoshi; Yamada, Akira
Abstract : We recently succeeded in controlling a Cu‐deficient Cu(In, Ga)Se2 layer (CDL) on a Cu(In, Ga)Se2 (CIGS) surface by introducing an Se irradiation after the completion of the second stage in a three‐stage process during CIGS growth. The CDL on the surface causes the formation of a valence band offset (Δ E V ) between the CDL and CIGS because the Cu vacancies decrease the valence band maximum of the CDL. Therefore, we can expect the suppression of recombination at the CdS/CIGS interface in CIGS solar cells due to the repelling of holes by Δ E V . The amount of knowledge regarding the properties of CDL/CIGS interfaces is observed to be quite small because a control technique for CDL has not been developed so far. In this study, the compositional and structural properties of an accurately controlled CDL/CIGS interface are investigated in detail. The composition of the interface between the CDL and CIGS is observed using an energy dispersive X‐ray spectroscopy with the help of a transmission electron microscope. Using nanobeam electron diffraction and Fourier transfer mapping analysis, it is confirmed that the ( 1 1 ¯ 2 ) plane in the CDL continuously grows on the ( 11 2 ¯ ) plane in CIGS. Further, these results indicate that a high‐quality interface is formed between the CDL and CIGS, which contains only a small amount of dangling bonds. Finally, a high conversion efficiency of 19.4% is achieved in the CIGS solar cell, which can be attributed to the formation of CDL and effect of Δ E V . Abstract : A high‐quality interface between a controlled Cu‐deficient Cu(In, Ga)Se2 layer (CDL) and a Cu(In, Ga)Se2 (CIGS) surface is demonstrated using Fourier transfer analysis for a transmission electron microscope image. The ( 1 1 ¯ 2 ) plane in the CDL continuously grows on the ( 1 1 ¯ 2 ) plane in CIGS, leading to only a small amount of dangling bonds at the interface and effectiveness of the CDL for high‐efficient CIGS solar cells.